Synthesis and Compressive Properties of Al-A206/SiC and Mg-AZ91/SiC Syntactic Foams - (:unkn) unknown (My University, 2013)
The objective of this thesis was to study the effects of matrix strength on the quasistatic compressive properties of syntactic foams using SiC hollow spheres as reinforcement and Aluminum A206 and Magnesium AZ91 as matrices. The SiC hollow microspheres syntactic foams were synthesized by a sub-atmospheric pressure infiltration technique and the resulting samples were then tested in compression at a strain rate of 10-3 s-1 using a conventional load frame. The energy absorbed by syntactic foams is represented by the area under the compressive stress-strain curve from the peak stress until densification again reaches the peak stress at a large strain. The peak strength, plateau strength and toughness of the foams studied increase with increasing yield stress of the matrix material. The increments for the peak stress were 13% for T4 and 24% for T7 treatments, referred to the as cast condition. For the same heat treatments, the increments for the plateau stress were 27% and 37%, while for the Toughness the values were 17% and 26% respectively.
Keywords: Aluminum Syntactic Foams; Magnesium Syntactic Foams; Metal Matrix Composites; Syntactic Foams